2020
DOI: 10.1093/advances/nmz107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition on Telomere Health: Systematic Review of Observational Cohort Studies and Randomized Clinical Trials

Abstract: Diet, physical activity, and other lifestyle factors have been implicated in the pathophysiology of several chronic diseases, but also in a lower total mortality and longer life expectancy. One of the mechanisms in which diet can reduce the risk of disease is with regard to its impact on telomeres. Telomere length (TL) is highly correlated to chronological age and metabolic status. Individuals with shorter telomeres are at higher risk of chronic diseases and mortality. Diet may influence TL by several mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 119 publications
3
58
0
1
Order By: Relevance
“…Our results are similar to another study using the same in vitro model and TATV R analysis which found that lutein mitigates telomere shortening under oxidative conditions (Mehkri et al 2019). Overall, our results demonstrating a protective effect of ergothioneine on telomere length under conditions of oxidative stress are in agreement with previous literature showing protective effects of other antioxidants on telomere length (Furumoto et al 1998;von Zglinicki et al 2000;Kiecolt-Glaser et al 2013;Freitas-Simoes et al 2016;Prasad et al 2017;Galie et al 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are similar to another study using the same in vitro model and TATV R analysis which found that lutein mitigates telomere shortening under oxidative conditions (Mehkri et al 2019). Overall, our results demonstrating a protective effect of ergothioneine on telomere length under conditions of oxidative stress are in agreement with previous literature showing protective effects of other antioxidants on telomere length (Furumoto et al 1998;von Zglinicki et al 2000;Kiecolt-Glaser et al 2013;Freitas-Simoes et al 2016;Prasad et al 2017;Galie et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that supplementation with omega-3 polyunsaturated fatty acids reduced oxidative stress markers, and telomere length increased with decreasing omega-6:omega-3 ratio (Kiecolt-Glaser et al 2013). Further, a recent systematic review which examined the effects of nutrition on telomere health found that certain nutrients such as vitamins C, D, beta-carotene, omega-3s, dietary fiber, fruits and vegetable intakes, as well as healthy dietary patterns such as the Mediterranean diet may have positive and protective effects on telomere length (Galie et al 2020). Though some of the clinical studies have been small, they provide a growing body of evidence that specific nutrients, healthy diets, and interventions to reduce stress (both oxidative and psychological) can be effective for preserving telomere length in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available evidence suggests that some antioxidant nutrients, the consumption of fruits and vegetables, and Mediterranean diet are mainly associated with longer telomeres [ 48 ]. With regard to macronutrients and telomeres, total protein and carbohydrates have not been clearly associated with telomere length; whereas the quality of carbohydrates, and particularly dietary fiber, may have a potential beneficial effect on telomere health [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of dietary fats on telomeres have been studied in more detail than the other macronutrients. Although the overall relation of monounsaturated fatty acids and PUFAs with telomere length is inconsistent [ 48 ], most studies have demonstrated a positive relation between n-3 PUFAs and telomere length in adult chronic diseases [ 51 53 ]. Differently, a study on Chinese adults reported that n-6 PUFAs are positively, but n-3 PUFAs are negatively associated with leukocyte telomere [ 54 ].…”
Section: Discussionmentioning
confidence: 99%